A Comparison of post-COVID vaccine myocarditis classification using the Brighton Collaboration criteria versus (United States) Centers for Disease Control criteria: an update - Slater, Kevin M; Buttery, Jim P; Crawford, Nigel W; Cheng, Daryl R (Communicable Diseases Intelligence, 2024)
Myocarditis associated with coronavirus disease 2019 (COVID-19) vaccination is a known adverse event following immunisation (AEFI). The lack of a singular diagnostic marker or test for myocarditis, besides the now infrequently undertaken histological diagnosis from biopsy, means that a combination of criteria is often needed to confirm a diagnosis. We have previously compared various international case definitions used to support accurate diagnosis and therefore standardise treatment and management of myocarditis.1 As more information about this important AEFI has come to light, some case definitions have been refined to provide greater sensitivity. Since our initial findings,2 the Brighton Collaboration (BC) Myocarditis/ Pericarditis working group have published updated diagnostic criteria.3 An important specific update is that a reported case with symptoms consistent with myocarditis, combined with abnormal cardiac medical resonance imaging (CMR), is now classified as a ‘probable’ case using the BC criteria – even in the absence of a raised troponin level. This therefore brings the BC definition for a Level 2 or ‘probable’ case in line with a ‘probable case’ using the United States Centers for Disease Control and Prevention (CDC) criteria (Table 1).4 Given these edits, this paper aims to refine our previous findings using updated diagnostic criteria, and to evaluate if there remain discrepancies in diagnosis and data reporting between the CDC (June 2021) and BC (June 2022) criteria.